FACTORS INFLUENCING THE UVEUHOOD INDEX AND LEVEL OF ASPIRATION OF FISHERWOMEN
A study was conducted among fifty women fish vendors in Kancheepuram and Chennai districts tL determine the factors influencing the livelihood index and level of aspiration. The independent variables such as annual income, scientific orientation, expenditure per year and savings per year were found to have highest factor loadings on livelihood index and level of aspiration of fisherwomen. Besides most of the fisherwomen had a high level (score of< 50) of livelihood index and a high level (score greater than 13